Analisis Model Bisnis Hotel XYZ - Wisnusanjaya, Adhityarama; Munir, Ningky Sasanti (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2021)
The growth of tourists to visits Bali area provide bright opportunities for the hotel industri. The intense level of price competition arises due to the large number of hotel developments taking place and the large number of un-used rooms. Hotel XYZ is one of the hotels in Bali with a strategic location. Fierce competition has the effect to difficulty determining the appropriate strategy. This research aims to analyze the business model of Hotel XYZ using Model bisnis kanvas(BMC) and formulate a new strategy for 2021-2022 using PEST (Politic, Economy, Social, Technology), Porter's Five Forces, and TOWS analysis. This research is an applied research using qualitative methods and analysis studies conducted at Hotel XYZ Bali and data collecting through by interviews, observations and literature studies. It was found that Hotel XYZ needs to add some BMC strategies such as maintaining the implementation of they CHSE (Cleanliness, Healthy, Safety, Environmental sustainability), improving ADR (Average Daily Rate) by continuously improving they service and products, renovating rooms to look fresh by changing wallpapers and headboards, sales teams need to more carefully to choose customer segments that earn more revenue than just customer volume. In addition, the need for top management cooperation with all its ranks in order to be dynamic when needed, especially difficult times in hard competition.